2016
DOI: 10.13168/agg.2016.0026
|View full text |Cite
|
Sign up to set email alerts
|

Application of PSInSAR for assessment of surface deformations in post_mining area _ case study of the former Walbrzych Hard Coal Basin (SW Poland)

Abstract: The study presents results of surface displacements calculated with the PSInSAR technique for the area of the former Wałbrzych Hard Coal Basin (WHCB) in SW Poland. Underground mining of hard coal took place there until the late 90'ties of the 20 th Century. In accordance with the present state of knowledge, secondary deformations are a common phenomenon on post-mining areas. The chosen monitoring technique has provided data and has allowed study surface movements in Wałbrzych in the post mining period, for whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Numerous approaches can be used to analyze and visualize ground movements in coal mining fields: statistical analysis of PS points [32] or PS points congruent to reference units [33] and also interpolation [34] with the aim of indicating areas of statistically-significant values of upward or downward ground movements with the aid of GIS-based hot spot analysis. The latter was also included in our paper.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous approaches can be used to analyze and visualize ground movements in coal mining fields: statistical analysis of PS points [32] or PS points congruent to reference units [33] and also interpolation [34] with the aim of indicating areas of statistically-significant values of upward or downward ground movements with the aid of GIS-based hot spot analysis. The latter was also included in our paper.…”
Section: Resultsmentioning
confidence: 99%
“…This activity was induced by sharp movement of the fault walls of both strike-slip and normal faults [25]. At the same time, the influence of rock massif collapse was also eliminated [29], as well as the effects of surface deformation of areas linked with former mining activity [30,31] in the neighbouring areas…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…In case of the Ostrava site, the entire area has experienced gradually decreasing subsidence, and in the case of the Odra mine, stabilization and gentle uplift in the second period (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010) that was analysed with Envisat data. For the Wałbrzych site, results of a study described in Milczarek et al (2017) complicated geological and mining conditions and unfavourable economic circumstances. Knowledge from other former mining sites suggested that these sites may experience ground motions following the end of mining.…”
Section: Discussionmentioning
confidence: 99%
“…Milczarek et al (2017) applied Envisat data and the PSInSAR technique to determine ground movements in urbanised parts of Wałbrzych for 9/2002 -7/2009 period. The results indicated an uplift of the surface within boundaries of former mining areas of up to 6 mm/year and on average 4 mm/year.…”
Section: Introductionmentioning
confidence: 99%